Unveiling Millennials’ Motivations to Purchase Smartwatches - Shamsi, Mohd Salman; Verma, Anuj; Verma, Meenakshi (Indian Journal of Marketing, 2023)
Purpose : This study used the unified theory of acceptance and use of technology 2 (UTAUT2) model to try and find the antecedents to behavioral intention among millennials to buy smartwatches. We looked into the variables influencing millennials’ intention to acquire smartwatches because of their growing propensity to embrace and use them. Methodology : A mixed method approach was used, with a qualitative study assisting in the identification of significant elements and a quantitative investigation (using structural equation modeling) analyzing the links that were suggested. Using AMOS 29 and Process Macro, data from 240 valid responses were used to test the hypotheses. Findings : We discovered that behavioral intention was significantly impacted by performance expectancy, social influence, brand enthusiasm, and hedonic motivation but not significantly by effort expectancy, price value, or facilitating conditions. Additionally, the moderating influence of both gender and educational attainment was investigated. Practical Implications : Manufacturers were advised to concentrate on the functional advantages of their products in order to draw in millennial customers. Extra effort should be made to cultivate a favorable perception among the purchasers. To improve the perception of smartwatches, brand-building campaigns had to be implemented. Originality : In contrast to earlier studies, the current work examined consumers’ views of smartwatches by extending the UTAUT2 model.